(untitled) (International Journal of Engineering and Computer Science, 2017)
Mobile ad hoc network(MANET) is a self deployed system of nodes which are free to mobile any where in the network. MANET does not require fixed infrastructure or centralized administration such as base station or access node. Nodes in the network work as host as well as router to forward the data via wireless links. Multiple senders and receiver are involved in the communication because no direct connection between the nodes as result of this security is essential in the MANET. Rushing attacks is also a type of security major in the MANET. Rushing attack cause the node to keep is isolate and scarce legitimate user in the MANET. In the MANET multicasting is widely used in multicasting one source node send data to many nodes as consequence of this multicasting transmission cost is reduced. But major drawback here is that while sending packets to multiple nodes mobile ad hoc network become unprotected because any node can be malicious node. There are different type of attacks in the MANET for example rushing attack, black hole attack, jelly fish attack, neighbor attack.This paper is based on rushing attack. In rushing attack the attacker quickly forward the packet in order to get easily access the route discovery path so that the attacker easily get the information of the network and resist all other valid node to get correct information. Once the route established between attacker and the destination all the information received by the destination will false or tempered. In MANET once the established every time data transmission path will be the same. In this paper we have proposed Rushing Attack Prevention Algorithm For MANET Using Random Route Selection to make DSR and AODV more efficient. This is time based approach also. This algorithm has removed some drawback of DSR and SDSR algorithm and it can be more efficient.